Molecular barcoding of an atypical cyprinid population assessed by cytochrome b gene sequencing - Chiesa, Stefania (2019)
A fish population of the carp family Cyprinidae with atypical phenotypic characteristics was observed in one of the main catchments of the Pollino National Park, a valuable, protected area in southern Italy. In this area, the Italian roach Rutilus rubilio (Bonaparte, 1837), a native endemic fish of Tyrrhenean regions, has been introduced in sympatric conditions with Squalius squalus (Bonaparte, 1837) and Telestes muticellus (Bonaparte, 1837). A molecular investigation was carried out to assess the genetic identity of the population with a view to conservation. Direct sequencing of a cytochrome b gene fragment was performed based on 30 individuals of cyprinid fish with atypical phenotype, in addition to 30 S. squalus, 10 T. muticellus, and 30 R. rubilio pure individuals collected in different Italian regions, which served as reference samples. Multiple sequence alignments demonstrated that 50% of atypical-cyprinid haplotypes were maternally inherited from either S. squalus or R. rubilio. No contribution by T. muticellus was determined. Our results indicate an intergeneric hybridization event between S. squalus and R. rubilio, as a consequence of trans-introduction activities of alien species.